The Role of Artificial Intelligence in Finnish B2B Marketing Agility - Harju, Lotta; Viertamo, Veera (2025)
This thesis explores how artificial intelligence (AI) enhances marketing agility (MA) in Finnish business-to-business (B2B) organizations. As dynamic markets and increasing data complexity challenge traditional marketing approaches, agility has emerged as a critical capability. Marketing agility refers to a firm’s ability to sense changes, respond rapidly, iterate continuously, and make data-driven decisions. Despite growing interest in AI, its specific role in supporting these agility dimensions in B2B settings remains under-researched.